Analysis of Grain Based Distilleries in Northern and Western Maharashtra - Patil, D. Y.; Khanna, Kamini; Deshmukh, Digvijay (Indian Journal of Marketing, 2019)
The food processing industry mostly depends on agriculture and has tremendous significance in human life and its evolution. The present study covered one of the important issues, that is, working of grain based distilleries in Northern and Western Maharashtra. The objective of this paper was to study the problems faced by grain based distilleries in Maharashtra. Factor analysis was used to assign weights to each variable and extract five factors. The results revealed that finance and production were the most important factors affecting their working. The government and policy makers will find the study to be helpful in policy making and can make improvements in weak and neglected areas of the food processing industry. It would be further beneficial to the thinkers, research scholars, academicians, and government officials interested in the food processing industry.